2021
DOI: 10.3390/ani11010101
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Tibia Shape in Organically Reared Chicken Lines Measured by Means of Geometric Morphometrics

Abstract: In the present study, the conformation of the tibia of seven genetic lines of broilers was analyzed by Geometric Morphometrics and correlated to carcass weight and walking ability. The used chicken genetic lines were classified as fast, medium, or slow growing and ranked for their walking ability. Six chicken types were reared in an organic farm and slaughtered at 81 days of age while one slow-growing and highly walking line (Naked Neck) was reared in a commercial farm and used as external reference for moving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
(28 reference statements)
0
9
0
2
Order By: Relevance
“…Mancinelli et al [ 6 ] demonstrated that although a prerequisite of adaptability to ERS is a daily weight gain (DWG) below 45 g/d, the genotype can also affect this adaptability. Accordingly, slow weight gain is a prerequisite of adaptation, but SG chickens also differ in other aspects, such as walking and foraging behavior [ 8 , 9 , 12 , 13 ], demonstrating that interest in outdoor spaces strongly depends on the intrinsic behavior and genetics of animals.…”
Section: Introductionmentioning
confidence: 99%
“…Mancinelli et al [ 6 ] demonstrated that although a prerequisite of adaptability to ERS is a daily weight gain (DWG) below 45 g/d, the genotype can also affect this adaptability. Accordingly, slow weight gain is a prerequisite of adaptation, but SG chickens also differ in other aspects, such as walking and foraging behavior [ 8 , 9 , 12 , 13 ], demonstrating that interest in outdoor spaces strongly depends on the intrinsic behavior and genetics of animals.…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that the estimated improvement in animal welfare in OPP is achieved only if the right genetic chicken line is chosen [ 5 , 54 , 64 , 65 , 66 ]. As already shown in Section 2.1 , fast-growing broilers at an older age (81 d) are very heavy and have an unbalanced body conformation as a result of intense genetic selection for additional breast muscle and body mass, which render kinetic activity more difficult and unusual.…”
Section: Methodology Of the Literature Reviewmentioning
confidence: 99%
“…As already shown in Section 2.1 , fast-growing broilers at an older age (81 d) are very heavy and have an unbalanced body conformation as a result of intense genetic selection for additional breast muscle and body mass, which render kinetic activity more difficult and unusual. Many studies have recommended the use of slow-growing strains in OPP, which do not have the same welfare problems of the current commercial strains [ 5 , 65 , 67 ]. Slow-growing strains have lower mortality, less incidence of leg weakness and cardiovascular diseases, and generally show an improved welfare status [ 68 ].…”
Section: Methodology Of the Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tulang tibia adalah bagian anggota badan yang terdiri atas tulang tibia dan tulang fibula serta melakukan persendian secara langsung di ventral dengan tulang tarsal dan membentuk sendi tibiotarsal. Tulang tibia berfungsi untuk menopang tubuh ayam dan morfologi tulang tibia dipengaruhi oleh bobot badan badan ayam (Pulcini et al 2021). Koni dan Foenay (2015) menyatakan bahwa umbi AC fermentasi dengan ragi tempe dapat digunakan hingga 5% dalam pakan ayam pedaging.…”
Section: Pendahuluanunclassified